Mapping Foodscapes for Dietary Change to Promote Sustainable Diets in Rural Farming Communities in Tunisia - Ghazel, Sabir (International Center for Agricultural Research in the Dry Areas, 2023)
With the ever-increasing rates of malnutrition, both overnutrition and undernutrition, improving agricultural and consumption practices globally plays a critical role in supporting sustainable diets. Sustainable diets have been defined as “diets with low environmental impacts which contribute to food and nutrition security and to healthy life for present and future generations [and which are] protective and respectful of biodiversity and ecosystems, culturally acceptable, accessible, economically fair and affordable; nutritionally adequate, safe and healthy; while optimizing natural and human resources” (Pimbert & Lemke, 2018). To discover appropriate opportunities to support sustainable diets, the foodscape of the target areas and populations should be studied. The term foodscape has been approached from any of the four broad perspectives namely spatial, sociocultural, behavioural, and systemic (Vonthron et al., 2020). A foodscape assessment entails not only looking at the community food environment, the spatial approach, but also at the food experiences of the targeted population, the socio-cultural approach. For the purposes of the current study, the foodscape of select rural communities in Tunisia, where agroecological interventions are planned to be initiated, was studied taking a spatial and sociocultural approach. The elements of foodscapes studies as per Turner et al. (2018) include: availability, diversity, accessibility, prices and affordability, vendor and product properties and convenience, marketing, promotion, quality, and regulation. These components are considered in the present study in Tunisia whose population faces nutrition-related adverse conditions. The sustainability of the Tunisian’s diets is challenged from not only an environmental perspective with high consumption of foods of animal origin with unequal distribution throughout the country (Perignon, 2019), but also from a nutritional perspective. Indeed, overnutrition in Tunisia has risen to a higher rate, 37.2% among women aged 18 years and over, than that of undernutrition with 8.4% of children under 5 years stunted and 2.1% suffering from wasting (Global Nutrition Report, 2021). Micronutrient deficiencies such as vitamins A, D and iron deficiency anemia (Doggui et al, 2020; Salem et al, 2021) indicate poor quality diets with possibly low nutrient density. Of the nutrition strategies’ indicators listed for Tunisia, no food-based dietary guidelines have been implemented. Adult females overall have a higher rate of both underweight and overweight and obesity compared to their male counterparts (Global Nutrition Report, 2021), which indicate gender imbalance in nutritional status with women being more adversely affected than their male counterparts. Whether the same nutritional status indicators prevail among rural farmers is not known. Recent evidence has pointed to positive effect of majority of agroecological interventions on food security and nutrition (Kerr et al., 2021). The interventions have looked into dietary diversity as an indicator of adequate nutrients in the diet of participants. However, the commonly used measures of dietary diversity, Minimum Dietary Diversity for Women (FAO & FHI, 2016) has focused on adequacy of nutrients rather than taking into account the consumption of foods high in calories and low in nutrients whose consumption should be limited. This is particularly important in the face of increasing rates of obesity. A simplified dietary quality questionnaire (DQQ) developed and validated for Tunisia (Gallup et al., 2022 & Uyar et al., 2023) was released in 2022 for use as a tool in assessing the dietary quality of Tunisians with other adaptations for other countries. The promotion of sustainable diets requires information about the factors that influence food-related decision making. Thus, observing the foodscape elements like food prices, which has witnessed a 12.9% rise over a year in October 2022 followed by a steep 13% increase in one month alone in November 2022 in Tunisia (Trading Economics, n.d.), is critical. Thus, the present study of foodscapes in rural Tunisia is multi-component including a market survey including both environmental survey of available foods and their prices in the market, restaurants review, snack foods assessment, availability of various facilities and resources in the communities such as schools, hospitals and paved roads and the voice of research participants related to food behaviour beliefs and perspectives on nutrition. The participatory nature of developing a food behaviour intervention that is effective and acceptable to partners is, thus, integrated from the initial stage of foodscape assessment and shall continue in future stages of potential food, nutrition and agroecological interventions. The purpose of this study is to present the foodscape of rural farming household communities in Tunisia. This understanding shall help guide the design of food behaviour change interventions to facilitate the adoption of sustainable nutritious diets.